Ethical aspects of GMO regulation in the EU: Regulating new plant breeding techniques as GM has negative effects on sustainability, diversity and inclusion. (28th July 2022) - Ramsay, Travis; Robinson, Benjamin; Coche, Isabelle; Hackett, Kristy; Emerson, Claudia
Abstract : Plant breeding plays a crucial role for the EU to live up to its values and promises of sustainability, innovation and diversity and inclusion. The current regulations, however, make it de facto impossible to use new breeding technologies.